Green project work for process writing amidst the pandemic: Planning, implementing, and reflections - Setyowati, Lestari; Karmina, Sari; Sukmawan, Sony; Razali, Razlina (citeus, 2022)
The aims of this paper are to discuss the concepts underlying Project-based learning (PjBL) and its syntax and to explore the planning, implementation, and reflection of PjBL in the online teaching of writing a process paragraph on the topic of using Reduce, Reuse, and Recycle (3R) principles to save the environment. Thirty-one students joined the paragraph writing course. The learning process and the students’ products of their projects were collected and documented in the form of videos, Power Point presentation, and electronic writing portfolios. The paper discusses how PjBl promotes collaborative work, problem-solving, critical thinking and technology integration. It also illustrates the steps of the implementation of PjBL which include planning, implementing, and reflecting. The project products were the students’ compositions and the videos showing the process in how to do or to make something that reflect the 3R principles. The majority of the students’ compositions were in ‘very good’ criteria, and the students’ videos were published in YouTube. The implementation of PjBL in the online teaching of process writing on the environmental topic increases the students’ critical thinking and creativity in solving global problems.